Measuring greenhouse gas emissions from smallholder systems - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
CCAFS-CIMMYT scientists are undertaking experiments to quantify greenhouse gas emissions from smallholder agriculture systems, in Karnal, Haryana. Researchers from CIMMYT and the Indian Council for Agricultural Research (ICAR) have brought out a guideline of protocols to standardize the methodology to carry out these tests.